The nutrition literacy gap among millennial mothers and its implications for the free nutritious meals program - Nabila Ayunisa Fajriani; Cita Lustriane; Aditya Lia Ramadona; Ruki Fanaike; Agus Yudi Prayudana (Universitas Gadjah Mada, 2026)
Purpose: This study aimed to analyze the nutrition literacy gap among millennial mothers from the housewives’ community participating in the Village Food Safety Movement (VFSM) Program and to explore its relevance to household practices beyond the scope of the Free Nutritious Meals (FNM) program. Methods: A descriptive one-group pre–post test design was conducted in 2024, involving 7,231 housewives (mean age: 35 years; classified as millennials) from 232 villages across 34 Indonesian provinces who were participating in the VFSM program. Participants were selected using purposive sampling with a consecutive approach based on predefined criteria. Data were collected using structured questionnaires, and descriptive analysis was used to assess the percentage of correct responses before and after the intervention. Results: The survey revealed a substantial knowledge gap. Correct responses to “What is stunting” (E1) and “The impacts of stunting” (E4) were moderate, ranging from 48% to 55%, while knowledge of “Types of foods that can prevent stunting” (E3) was very low, with scores below 25%. Descriptively, only limited improvements were observed after the intervention, and overall knowledge levels remained below the “adequate” threshold (>60%). These findings suggest limited improvement following the intervention and highlight the need for sustained educational efforts. Conclusion: The gap in practical nutrition literacy, particularly in identifying stunting-preventive foods, may influence the optimal utilization of the FNM program. As the program provides only 30–35% of daily energy needs, the remaining intake must be met through safe and nutritious foods prepared at home. Without sufficient knowledge of food safety and nutrition, this complementary intake may be inadequate. These findings highlight the necessity of practical, adaptive education—incorporating digital and visual methods—to strengthen household food safety and nutrition practices in support of the FNM program.